Trigonal Nitrogen Activates High-Brightness Chemiluminescent Carbon Nanodots - Shen, Cheng-Long; Lou, Qing; Lv, Chao-Fan; Zheng, Guang-Song; Zang, Jin-Hao; Jiang, Tian-Ci; Cheng, Zhe; Liu, Kai-Kai; Niu, Chun-Yao; Dong, Lin; Shan, Chong-Xin (ACS materials letters, 2021)
Chemiluminescence (CL) has intrigued extensive interest, because of its promising applications as a cold light illuminator and in bioimaging. However, relatively low brightness and high biotoxicity of traditional CL materials such as dyes obstruct their applications. Herein, with the merit of the energy level alignment between the carbon nanodots (CDs) and the energy-rich intermediate generated in the peroxalate system, we design a facile controllable nitrogen doping route to prepare CDs for high-brightness CL. The increased amount of trigonal nitrogen restructures the CDs from a graphitic carbon core to a β-C3N4 core, which triggers the lifting of the highest occupied molecular orbital and further promotes the electron exchange between the CDs and intermediate agents. Meanwhile, the restructured bonding and antibonding molecular orbitals lead to the tunable CL emission wavelength. Thus, a maximal luminance of 4.35 cd m–2 has been achieved in the CL CDs with high nitrogen content, which is the highest value ever reported previously. Besides, the CL luminophore in cold illumination and CL probes for cellular reactive oxygen species imaging have been demonstrated with these CDs. These results may provide a route to high-brightness chemiluminescent nanomaterials in displaying and bioimaging.